Spatial and Multilevel Analysis of Unscheduled Contraceptive Discontinuation in Ethiopia: Further analysis of 2005 and 2016 Ethiopia Demography and Health Surveys - Koku Sisay Tamirat; Solomon Gedlu Nigatu; Getayeneh Antehunegn Tesema; Malede Mequanent Sisay; Zemenu Tadesse Tessema (Frontiers Media S.A., 2023)
BackgroundUnscheduled discontinuation of contraceptives is a public health problem among women of reproductive age. Particularly, it is associated with unwanted pregnancies that lead to maternal and child mortality, but little is known about the spatial distribution of the problem. Therefore, this study aims to assess the spatial distribution and associated factors of unscheduled contraceptive discontinuation in Ethiopia.MethodThis study used secondary data from the Ethiopia Demography and Health Survey (EDHS) data of 2005 and 2016. The study population was women who used contraceptives in the preceding 5 years before the survey. A total of 2,327 and 3,858 eligible women were included in the final analysis of the 2005 and 2016 EDHS, respectively. For the spatial analysis, both the 2005 and the 2016 EDHS data were analyzed using ArcGIS version 10.7, while for multilevel regression analysis, the 2016 EDHS data were used. The final model reported an adjusted odds ratio (AOR) with a 95% confidence interval (CI), and a p-value of 0.05 was used to declare statistical significance.ResultThis study revealed that unscheduled discontinuation of contraceptives varied geographically, and hotspots were detected in the central, north, and eastern parts of Ethiopia. Moreover, diploma and higher education (AOR = 1.40; 95% CI: 1.01-1.95), urban residence (AOR = 1.37; 95% CI: 1.08-1.72), history of termination of pregnancy (AOR = 1.47; 95% CI: 1.14-1.94), married women (AOR = 10.79; 95% CI: 6.98-16.69), separated/divorced women (AOR = 1.54: 95% CI: 1.07-2.30), -two to four number of children (AOR = 1.46; 95% CI: 1.15-1.84), and involvement in the decision-making process of contraceptive use (AOR = 39.26; 95% CI: 28.84-53.45) were all factors associated with unscheduled discontinuation of contraceptives.ConclusionThis study revealed that unscheduled discontinuation of contraceptive distribution was significantly clustered in the central, north, and eastern parts of Ethiopia, as found in two surveys. The magnitude of this discontinuation increased from 2005 to 2016. The finding underscores that further interventions such as the availability of multiple mixed methods and improvement in women's decision-making ability in the choice of contraceptive methods and utilization are needed in hotspot areas of Ethiopia.